"Feeling the force" in reproduction: Mechanotransduction in reproductive processes. (3rd May 2016) - Evans, Janice P.; Leppert, Phyllis C.
ABSTRACT: Reproductive biologists are well-versed in many types of biochemical signaling, and indeed, there are almost innumerable examples in reproduction, including steroid and peptide hormone signaling, receptor-ligand and secondary messenger-mediated signaling, signaling regulated by membrane channels, and many others. Among reproductive scientists, a perhaps lesser-known but comparably important mode of signaling is mechanotransduction: the concept that cells can sense and respond to externally applied or internally generated mechanical forces. Given the cell shape changes and tissue morphogenesis events that are components of many phenomena in reproductive function, it should be no surprise that mechanotransduction has major impacts in reproductive health and pathophysiology. The conference on "Mechanotransduction in the Reproductive Tract" was a valuable launch pad to bring this hot issue in development, cell biology, biophysics, and tissue regeneration to the realm of reproductive biology. The goal of the meeting was to stimulate interest and increased mechanotransduction research in the reproductive field by presenting a broad spectrum of responses impacted by this process. The meeting highlighted the importance of convening expert investigators, students, fellows, and young investigators from a number of research areas resulting in cross-fertilization of ideas and suggested new avenues for study. The conference included talks on tissue engineering, stem cells, and several areas of reproductive biology, from uterus and cervix to the gametes. Specific reproductive health-relevant areas, including uterine fibroids, gestation and parturition, and breast tissue morphogenesis, received particular attention.